Of Love and Papers How Immigration Policy Affects Romance and Family - Enriquez, Laura E. (University of California Press, 2020)
Of Love and Papers explores how immigration policies are fundamentally reshaping Latino families. Drawing on interviews with undocumented young adults, Enriquez investigates how immigration status creeps into the most personal aspects of everyday life, intersecting with gender to constrain dating, marriage, and parenting. She illustrates how the imprint of illegality remains, even upon obtaining DACA or permanent residency. Interweaving the perspectives of US citizen romantic partners and children, she exposes the multigenerational punishment that limits the upward mobility of Latino families. Of Love and Papers sparks an intimate understanding of contemporary US immigration policies and their enduring consequences for immigrant families. "By highlighting the ways US immigration policies shape the experiences of romantic love, intimacy, and family formation, Enriquez's meticulous research calls attention to the enduring injurious effects on undocumented and DACAmented young adults, and on their citizen spouses and children. An innovative and sobering account of the far-reaching consequences of our punishing immigration policies. Timely and compelling." PIERRETTE HONDAGNEU-SOTELO, Florence Everline Professor of Sociology, University of Southern California "In an engaging and methodologically rigorous narrative, Enriquez sheds novel light on the courtship and dating phase of family formation among undocumented and/or mixed status Mexican immigrant families. Undeniably, it will be of central interest to anyone who cares about immigrants and their families." CECILIA MENJÍVAR, Professor of Sociology, University of California, Los Angeles